Effect of date fruits (Phoenix dactylifera) on human pathogenic bacteria: A systematic review - Farhana M.I.N.; Natasha A.; Shahida W.S.W.; Zetty Nadia Mohd Zain (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA